Concordance Test of Various Erythrocyte Indices for Screening of Beta Thalassemia Carrier - Reni Nurazizah; Renaldi Satria Handika; Edhyana Sahiratmadja; Yoyos Dias Ismiarto; Delita Prihatni (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Carrier screening for early detection of thalassemia in the general population needs a careful approach, especially in areas with limited health services. Various erythrocyte indices have been introduced as options for the first stage; however, the low-reliability value of these erythrocyte indices remains the problem. This study aimed to determine the most reliable index for screening beta-thalassemia carriers and distinguish it from iron deficiency anemia. A cross-sectional study was designed to explore thalassemia carrier status among medical students. Inter-rater reliability value of various indices was compared to Shine and Lal index. The Cohen's Kappa coefficient was calculated using SPSS v. 25.0. Among 320 respondents, 295 subjects were non-anemic and 25 were anemic subjects, whereas 105 subjects had low MCV and/or MCH values. Cohen's Kappa value showed moderate reliability results compared to Shine and Lal index for example Mentzer index (0.58), Ehsani index (0.57), Srivastava index (0.53), and Bordbar index (0.41), but showed very low-reliability results with Green and King index (0.04). New cut-off indices based on Kumar et al. were also compared, resulting in moderate reliability results. Since there was no Hb-electrophoresis test, the sensitivities and specificities of those indices could not be calculated. For this reason, a complete blood count can only be used for the early stages of screening for beta-thalassemia carriers, whereas Hb-electrophoresis and DNA tests were considered necessary to perform to confirm a diagnosis.